The Effects of Sharing Awareness Cues in Collaborative Mixed Reality - Piumsomboon, Thammathip; Dey, Arindam; Ens, Barrett; Lee, Gun; Billinghurst, Mark (Frontiers in Robotics and AI, 2019)
Augmented and Virtual Reality provide unique capabilities for Mixed Reality collaboration. This paper explores how different combinations of virtual awareness cues can provide users with valuable information about their collaborator’s attention and actions. In a user study (n=32, 16 pairs), we compared different combinations of three cues: Field-of-View (FoV) frustum, Eye-gaze ray, and Head-gaze ray against a baseline condition showing only virtual representations of each collaborator’s head and hands. Through a collaborative object finding and placing task, the results showed that awareness cues significantly improved user performance, usability, and subjective preferences, with the combination of the FoV frustum and the Head-gaze ray being best. This work establishes the feasibility of room-scale MR collaboration and the utility of providing virtual awareness cues.